Pengaruh Penggunaan Sistem Sekat Dalam Box Portable Atmospheric Water Generator Terhadap Unjuk Kerja Produksi Air, Efisiensi, COP, Pawg Sistem Alami - Suparlan, Maria D.C.; Jafri, Muhamad; TARIGAN, Ben Vasco (Universitas Nusa Cendana, 2023)
2.1 billion people can’t have access to water, and 4.5 billion with insufficient sanitation or clean water sources. While water is extremely useful for everyday, such as washing, cooking, bathing etc. So fulfillment of water needs must balanced with increase the addition of population can be fulfilled. this study, was carried out experimentally by testing on 2 variations media, media test with insulation and media test without insulation, at 30 minutes intervals, temperature was measured in box to identify factors affect condensation process at several points. Obtained from research analyze effect using partition system on PAWG indications for water production, efficiency, COP, natural PAWG systems for fresh water production within 24 hours from 2 variations of media and maximum Coefficient of Performance. Water amount production for 24 hour, the variation of media with changes in temperature and good COP is found in variation media with insulation, the highest temperature is 36.750C, the humidity value 66.3% and COP value 0.230769 and amount water production is 16 ml, and temperature change in variation of media without insulation with the highest temperature is 39.50C, humidity is 65.4% with a COP value 0.02 and the amount of water production is 12 ml.